2015
DOI: 10.1021/acs.joc.5b00237
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Transannular Cyclization Reactions To Synthesize Azabicyclo[X.Y.Z]alkanone Amino Acid Derivatives from 8-, 9-, and 10-Membered Macrocyclic Dipeptide Lactams

Abstract: An efficient method for synthesizing different functionalized azabicyclo[X.Y.0]alkanone amino acid derivatives has been developed employing electrophilic transannular cyclizations of 8-, 9-, and 10-membered unsaturated macrocycles to form 5,5-, 6,5-, 7,5-, and 6,6-fused bicylic amino acids, respectively. Macrocycles were obtained by a sequence featuring peptide coupling of vinyl-, allyl-, homoallyl-, and homohomoallylglycine building blocks followed by ring-closing metathesis. X-ray crystallographic analyses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 81 publications
0
21
0
Order By: Relevance
“…The latter was smothly protected as its methyl ester using methyl iodide in the presence of cesium carbonate to provide the desired 2-aminoheptenoic acid derivative 11 . Several syntheses of this important amino acid have appeared which include Lubell’s palladium-catalyzed allylation [ 15 ], Riera’s asymmetric epoxidation protocol [ 16 ], Rich’s enolate amination [ 17 ] and Hruby’s asymmetric alkylation [ 18 ] of a chiral nickel complex among others. Moreover, many of these studies have also reported an elegant use of this unsaturated amino acid [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The latter was smothly protected as its methyl ester using methyl iodide in the presence of cesium carbonate to provide the desired 2-aminoheptenoic acid derivative 11 . Several syntheses of this important amino acid have appeared which include Lubell’s palladium-catalyzed allylation [ 15 ], Riera’s asymmetric epoxidation protocol [ 16 ], Rich’s enolate amination [ 17 ] and Hruby’s asymmetric alkylation [ 18 ] of a chiral nickel complex among others. Moreover, many of these studies have also reported an elegant use of this unsaturated amino acid [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Instead of preparing both macrocycle and bicycle independently prior to their insertion into the analogs, transannular cyclization was employed to convert the macrocyclic peptide into its bicyclic counterpart. Although transannular cycliza-tions of N-protected macrocyclic lactam esters have been used to make various azabicyclo[X.Y.0]alkanone amino acid analogs, 23,28 successful application of this method within a larger peptide framework has not been previously reported.…”
Section: Resultsmentioning
confidence: 99%
“…23 Pyrroloazepinones 10a and 10b were respectively synthesized by diastereoselective transannular cyclizations of macrocyclic lactam 9 and its Fmoc counterpart using iodine in THF. 23,28 Instead of preparing ester 10a for subsequent introduction into a constrained analog by peptide coupling chemistry, a new strategy featuring transannular cyclization within the peptide framework was examined to introduce the azabicyclo-[5.3.0]alkan-2-one into peptide mimic 2. Macrocyclic peptide 13 was treated with iodine in the presence of excess sodium bicarbonate for 1 h (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…8 For instance, IBTM is an indolizidine dipeptide surrogate widely used to generate conformationally constrained β-turn mimics 9 and several analogs of it have been synthesized and investigated, showing diverse biological activities. 10 In this context, innovative methodologies for the synthesis of indolizidine and quinolizidine systems have been described, 11 wherein the regio-and stereochemical control of the substituent attachment is a main issue. Some of the described syntheses include alkylation reactions of cyclic iminium ions, mainly intramolecular, 12 and other encompass a ring closing metathesis (RCM) reaction.…”
Section: Accepted Manuscriptmentioning
confidence: 99%